Strategi Pengembangan Kurikulum di SMP Islam Terpadu Pondok Pesantren Al Madinah Boyolali - Tisnawati, Tin; Anshory, Isa (Lembaga Yasin AlSys, 2024)
Curriculum is an important tool in education. To improve the quality of education, curriculum development must be carried out comprehensively. This research aims to describe the curriculum development at Al Madinah Boyolali Integrated Islamic Middle School. The research method used in this research is a qualitative descriptive method, with a research approach in the form of a case study. The results of the research show that the curriculum at the Al Madinah Boyolali Integrated Islamic Middle School is an integrity curriculum, meaning an educational unit-level curriculum that combines the education service curriculum with the Saudi Arabian curriculum with superior tahfizhul Qur'an and Arabic language programs. The model of teaching and learning activities adopted at the Al Madinah Boyolali Integrated Islamic Middle School consists of two combined systems, namely the Salafiyah education system and the modern education system, namely that teaching and learning activities adhere to the school system in general. Four of the existing components include objectives, curriculum content, strategy, and evaluation. The objective component specifications relate to the four core competencies of graduates that must be mastered or achieved by the students of Al Madinah Boyolali Integrated Islamic Middle School, namely the core competency of monotheism, the core competency of having noble morals, the core competency of being intelligent, and the core competency of being competitive. The content components of the Al Madinah Boyolali Integrated Islamic Middle School curriculum are organized in three forms of activities, namely curricular, co-curricular, and extracurricular activities. The learning strategy component refers to the teaching approaches methods and equipment used in teaching. The curriculum evaluation component is intended to assess a curriculum as an educational program and determine the efficiency, effectiveness, relevance, and productivity of the program in achieving educational goals.